Outlier Analysis of the Buchanan-three-phase Model used in Fitting the Growth of Paracoccus sp. SKG on Acetonitrile (Journal of Environmental Bioremediation and Toxicology, 2015)
Organonitriles are widely used in industry such as the synthesis of plastics, rubber, herbicides, pharmaceuticals, drug intermediates, and pesticides. They are carcinogenic and mutagenic. Bioremediation of acetonitrile, an organonitrile, has been touted as a more economical and feasible method compared to physical and chemical approaches. In this work, we model the growth of growth of Paracoccus sp. SKG on acetonitrile from published literature to obtain vital growth constants. We discovered that the Buchanan-three-phase model via nonlinear regression utilizing the least square method was the very best model to explain the growth curve. However, the use of statistical tests to choose the best model relies heavily on the residuals of the curve to be statistically robust. More often than not, the residuals must be tested for the presence of outliers (at 95 or 99% of confidence). In this work, the Grubbâ€™s test to detect the presence of outlier in the growth model was carried out.
Keywords: acetonitrile-degrading, Buchanan-three-phase, Paracoccus sp. SKG, ordinary least squares method, Grubbs test